CARDIOPROTECTIVE ACTIVITY OF EMPAGLIFLOZIN AND LIRAGLUTIDE WITH OR WITHOUT METFORMIN IN DIABETIC RATS INDUCED BY ACUTE MYOCARDIAL INFARCTION - Sukaeningsih, Desi
DM patients with comorbid cardiovascular disease are recommended to use sodium glucose cotransporter-2 inhibitors (SGLT2i) and glucagon like Peptide 1 receptor agonist (GLP1-RA) which have been proven to reduce the risk of complications of myocardial infarction. In addition, metformin is also the "first line" for the treatment of DM and can significantly reduce the risk of acute IM. In this study, the effects of empagliflozin and liraglutide with or without metformin on DM and IM parameters in Wistar rats were examined. Animals were induced with Lipomed® 20% MCT/LCT at a dose of 20 ml/kgBW (i.g) followed by induction of streptozotocin (STZ) 55 mg/kgBW (i.p), then the IM model was induced with Isoproterenol (ISO) 85 mg/kgBW (i.p). Animals were treated according to groups, namely negative control (Na CMC 0.5% i.g), positive control (DM+IM); test group 1 (liraglutide 0.062 mg/kgBW s.c); test group 2 (empagliflozin 1 mg/kgBW i.g); test group 3 (metformin 87.8 mg/kgBW i.g); combination 1 (liraglutide 0.062 mg/kgBW s.c and empagliflozin 1 mg/kgBW i.g); combination 2 (metformin 85.7 mg/kgBW i.g; liraglutide 0.062 mg/kgBW s.c and empagliflozin 1 mg/kgBW i.g) for 30 days. Combination group 1 showed improvements in DM parameters (KITT value 0.96%/minute and GDP 108.67 mg/dL) and IM parameters with percentage inhibition (%) of the biomarkers creatine kinase (CK), CK-MB, aspartate transaminase (AST ), and alanine transaminase (ALT) respectively, namely 59.88%, 63.05%, 48.63%, 40.32%. Histopathological observations showed improvement in myocardial damage characterized by tight gaps between myocardial fibers and no cell infiltration was observed, while (%) the infarct area was (3.02%). SIRT-1 protein levels increased by (7.13 ng/mL). Meanwhile, combination 2 did not provide better results compared to combination 1 on DM parameters (KITT value 0.97%/minute and GDP 126 mg/dL) and IM parameters with CK, CK-MB, AST and ALT inhibitory percentages overall. sequentially, namely 57.07%, 58.54%, 41.59%, 33.08%. In histopathological observation, wide gaps between myocardial fibers were still observed and cell infiltration was observed, while the % of infarct area was high, namely (3.76%). Not only that, the SIRT1 protein level was detected less (6.09 ng/mL).